Numeric Evaluation on the System Efficiency of the EPC Gen-2 UHF RFID Tag Collision Resolution Protocol in Error Prone Air Interface. (9th March 2014) - Yan, Xin-Qing; Liu, Yang; Li, Bin; Liu, Xue-Mei
Abstract : Efficient resolution of the tag collisions is the key for the RFID systems to be universally adopted. To resolve the tag collision occurred in the UHF RFID system, the EPC Gen-2 protocol, proposed by the EPCglobal Inc., was adopted as an international standard and have been widely accepted in industry. However, little research works has been taken to evaluate the performance of this protocol in nonperfect and error prone air interface. In this paper, to evaluate the performance of the EPC Gen-2 protocol, a system efficiency model is proposed, and, based on the model, numeric simulations are performed to evaluate the EPC Gen-2 protocol in error prone air interface. Simulation results reveal that the system efficiency of the EPC Gen-2 protocol is seriously affected by the capture and noise effects.